Comparison between in vitro embryo production in Bos indicus and Bos taurus cows (Research, Society and Development, 2021)
The aim of this study was to evaluate the in vitro embryo production in Bos taurus and Bos indicus donors, evaluating from oocyte recovery to final embryo production. Data were collected during the months of January and February and August to October 2017. Bos taurus cows: Holstein and Senepol and Bos indicus cows: Nelore and Dairy Gir, were used as oocyte donors. In total, 3622 sessions of OPU were performed, divided between: Holstein donors: 925; Senepol donors: 1055; Nelore donors: 1202 and Dairy Gir donors: 440. In total, 103.399 oocytes were recovered, being viable oocytes: 90.807; cleaved: 65.252 and produced embryos: 24216. There was no statistical difference between the genetic groups for the total oocytes recovered (Bos taurus: 25.5 vs. Bos indicus: 30.1; P> 0.05). However, a statistical difference was observed between the cleaved (Bos taurus: 16 vs. Bos indicus: 20.4; P